THE EFFECT OF AEROBIC LOW IMPACT EXERCISE ON CHANGES IN BLOOD PRESSURE PATIENTS WITH HYPERTENSION - Nurul Pujiastuti; Mardina Tesalonika (Proceeding International Seminar of Islamic Studies, 2022)
One of the causes of hypertension is the narrowing of the blood vessels which results in decreased tissue perfusion. The purpose of this study was to determine the effect of low-impact aerobic exercise on changes in blood pressure in patients with hypertension. The research design used Quasy Experimental with a pre-test-post-test control group design. The research technique used non-probability sampling with a total sampling technique. The sample size was 36 respondents, divided into two groups, namely the treatment and control groups. The treatment group received low-impact aerobic exercise intervention three times per week for four weeks. Before the intervention, the respondent's blood pressure would be measured, and after the intervention. The result showed that was an effect of changes in blood pressure in patients with hypertension after participating in Aerobic Low Impact exercise for four weeks. Changes in blood pressure occur in both systolic and diastolic pressure. The average decrease in systolic blood pressure was 27.78 mmHg and the average decrease in diastolic blood pressure was 20.55 mmHg. The results of the Wilcoxon test with p-value = 0.000 or (p0.05), showed that there was a significant change between systolic and diastolic blood pressure, before and after the intervention. Low Impact Aerobic Gymnastics can affect changes in blood pressure, so this exercise can be used as a non-pharmacological therapy and a companion to pharmacological therapy in the management of hypertension.Keywords: aerobic low impact exercise, blood pressure, hypertension